PENANDA KATA GANTI ORANG DALAM BAHASA TERNATE - Ety Duwila; Nurfani Nurfani (Kantor Bahasa Provinsi Maluku Utara, 2019)
This research is aimed ti describe marker of personal pronouns in Ternate language. As an ethnic language, Ternate language has its own uniqueness. Ternate language has the unique grammatical that is different from other languages. By using the descriptive qualitative methods, this study succeeded in revealing that in Ternate language there were forms of pronouns, namely fajaru, fangare, ngori, ngom, ngone, ngon, ngana, una, mina, and ana which are free morphemes, so that in sentences can stand alone and in active voice fill the function of Subject (S). In addition, in this language there are also markers of personal pronouns whose position both in speech and grammatically cannot stand alone in sentences but are attached to other forms. However, this bound form has a lexical meaning, which is a marker of personal pronouns. The markers of BT pronouns are: to- (marker of first singular personal pronoun), mi- (marker of first plural exclusive personal pronouns), si- (marker of first plural inclusive personal pronouns), no- (marker of second singular personal pronouns), no- (marker of second plural personal pronouns), o- (marker of third singular personal pronoun), and i- (marker of third plural personal pronoun).